The Realist and Liberal Positions on the Role of International Organizations in Maintaining World Order - Ersan Ozkan; Hakan Cem Cetin (European Scientific Journal, ESJ, 2016)
In the international relations (IR)’ theoretical and empirical studies, international regime studies emerged as a reaction to inadequacies of the concepts of authority, international order and organization. Over more than half a century, realism has been skeptical of international law. In both classical and neorealist approaches, states are depicted as seeking to maximize power and producing a balance of power. This study examines two paradigms, realism and liberalism, in an attempt to take a closer look at what each of these schools has to offer to the international relations. To be able to carry out such an evaluation each of these paradigms will be analyzed with respect to their positions on the following principles: unit of analysis, key concepts, behavioral dynamics, interstate system, peace and war, and last but not least explanatory power. Discussing the strengths and weaknesses of each of these paradigms will help in determining which of these approaches is the most persuasive.